PERANCANGAN ANIMASI 2D SEBAGAI SALAH SATU MEDIA DALAM MEMPERKENALKAN MORAL HIDUP MELALUI CERITA FIKTIF - Sastro Lino, Felix; Adnas, Diny Anggraini (Universitas Nusa Cendana, 2024)
Animation 2D is one of the media that has been used for several purposes during this period. Animation 2D is use as study media in most of the schools, but the template is always the same which is similar to Powerpoint slide-show to deliver information or knowledge, especially moral and character-building values. This method that’s usually often use may give impression to viewers that Animation 2D is monotonous. Animation 2D should be delivered in a more different kind of ways in order to attract and interest the viewers, like fiction story. Many knowledges or information, especially moral and character-building values can be delivered through story, because the story itself may entertain and increase the interest of the viewers to watch and it may become one of the entertaining media for viewers. Method used on the research is Multimedia Development Life Cycle (MDLC) which consists of 6 steps such as concept, design, material collecting, assembly, testing, and distribution. The result is the animation 2D fiction story get most people interests, especially teenagers in the age range around 14-18 years old and can deliver moral message implicitly. Animation 2D media can still be further developed into films with detailed story so that it can leave deep impression dan can be understood more by audiences, especially teenagers. By increasing the audience’s understanding of the 2D Animation content story, it may indirectly leave moral message that is quite impressive for the teenagers.